Chemical attributes of soils managed by a sugar and alcohol plant located in Nova Alta Paulista (Research, Society and Development, 2021)
Sugarcane is considered a renewable and clean energy matrix, which has led to the expansion of cultivated areas. The large amount of phytomass produced by the crop requires an adequate supply of water and nutrients, so the diagnosis and management of soil fertility is of fundamental importance. The chemical analysis of the soil is one of the main tools for this, as it allows the quantification of the chemical attributes of the soil that serve as a basis for the application of fertilizers, soil amendments and conditioners, enabling sustainable and economically viable production. This study aimed to evaluate the chemical attributes of soils managed by a sugar and alcohol plant in Nova Alta Paulista. In 1120 soil samples the pH, CTC, base saturation and the contents of organic matter and macronutrients were analyzed, and in 280 samples the micronutrient content was also analyzed. The results were presented graphically with the distribution of values expressed as a percentage. The average and the most frequent value, represented by fashion, were also calculated. It was found that in general the soils evaluated have low content of organic matter. The results indicate that the soils are frequently corrected with the application of lime and suggest a constant monitoring of the K, S, B and Zn contents so that these nutrients can be carefully provided, allowing the maintenance or increase of soil fertility and productivity of sugar cane.